Recent Advances in Information Systems and Technologies Volume 3 - Rocha, Álvaro; Correia, Ana Maria; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents a selection of papers from the 2017 World Conference on Information Systems and Technologies (WorldCIST'17), held between the 11st and 13th of April 2017 at Porto Santo Island, Madeira, Portugal. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges involved in modern Information Systems and Technologies research, together with technological developments and applications. The main topics covered are: Information and Knowledge Management; Organizational Models and Information Systems; Software and Systems Modeling; Software Systems, Architectures, Applications and Tools; Multimedia Systems and Applications; Computer Networks, Mobility and Pervasive Systems; Intelligent and Decision Support Systems; Big Data Analytics and Applications; Human-Computer Interaction; Ethics, Computers & Security; Health Informatics; Information Technologies in Education; and Information Technologies in Radiocommunications.
Immersive journalism through mobile devices: how virtual reality apps are changing news consumption -- Crowdfunding: a possible complementary funding model for European public service broadcasting -- Uses and trends of social networks by public service media in Europe -- Independence: the cornerstone of public service media governance -- Social media communication as a corporate positioning strategy: the Galician winemaking sector in Spain -- Realistic Boccia Game Simulator Adapted for People with Disabilities or Motor Disorders: Architecture and Preliminary Usability Study -- Determinants of Facebook adoption and use within the workspace in Cameroonian universities -- An Initial Proposal for a Web 2.0 Information System that Supports a 360º Customer Loyalty Assurance Process in Private Healthcare Organization -- Using Online Recruitment: implicit theories and candidates' profile -- Classroom and Interactivity: New Spaces with an Interactive Computer Operating System Customization -- Toward a Smart Health-care architecture using WebRTC and WoT -- 3D Scanner Based on an Autonomous Wi-Fi Unmanned Mini Quadcopter -- Standardization of Policies of the Use of Distance Aircraft Systems and Aircraft Systems (RPAS / UAS) in Ecuador.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence